Prevalence, persistence, clearance and risk factors for HPV infection in rural Uyghur women in China - Gulixian Tuerxun; Guligeina Abudurexiti; Guzalinuer Abulizi (BMC, 2023)
Abstract Background The incidence of cervical cancer in Uyghur women ranks first among those in Han and other ethnic minority groups. We aimed to understand the natural history of HPV in Uyghur women. Methods A longitudinal cohort study on the natural history of HPV infection in rural Uyghur women in China was conducted between May 2013 and May 2014. A total of 11000 women from South Xinjiang underwent HPV screening by careHPV and liquid-based cytology. Ultimately, a total of 298 women with positive HPV and normal biopsy results or CIN1 were enrolled to participate in a study including follow-up HPV testing for two years. Results The HPV infection rate in Uyghur women was 9.15%. Among the participants, the careHPV test showed that 298 women were HPV-positive, and histology showed CIN1 or normal results for these women at baseline. Among these patients, after 24 months of initial recruitment, 92 (30.87%) patients had persistent HPV infections, and 206 (69.13%) had cleared HPV infection. Univariate analysis showed that persistent HPV infection was associated with age and shower frequency (P < 0.001 and P = 0.047, respectively). Conclusions Our results suggest that women over the age of 50 years who have been infected with HR-HPV for more than 1 year should be regularly screened and monitored for HPV. In addition, education should be strengthened to improve poor health habits in these women.